Standardization of Eel Rendang Recipe in Tanjung Baru - Gusnita, Wiwik; Kasmita, Kasmita; Holinesti, Rahmi; Insani, Ranggi Rahimul (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
This study aims to standardize the Eel Rendang recipe in Tanjung Baru District, Tanah Datar Regency, which includes ingredients, spices, tools, benefits, and processing methods. It also analyses shape, color, aroma, texture, and taste quality. The background of this study is the unequal and highly diverse quality of Eel Rendang produced in Tanjung Baru District due to variations in the use of basic spices, cooking methods, and doses. In addition, this sub-district is one of the regions that regularly produces Eel Rendang, has UMKM (small and medium enterprises) that consistently produce Eel Rendang, has a sufficient area for rice fields, and is one of the regions that frequently use Eel Rendang in different traditional events. This type of research is a mixed method. Five trained panelists who were knowledgeable about Rendang in terms of the concept and the processes for processing Eel Rendang served as the quantitative data sources. Qualitative data were gathered from persons who are experts at producing Rendang. The standard recipe for Eel Rendang covers the primary components, seasonings, equipment, processing methods, and quality based on the findings of this study. Based on its advantages, Eel Rendang is frequently used in customary occasions, including weddings, batagak penghulu, bathing celebrations, akikah festivities, and for daily consumption. The standard recipe for Eel Rendang passed the organoleptic test with flying colors: it was long enough, somewhat blackish brown, quite aromatic, with a dry, oily texture to the bran and flesh, as well as a pervasive spice flavor and savory bran flavor.